High-grade central mucoepidermoid carcinoma arising in an odontogenic cyst: a case report and review of the literature - Świerzy, Paweł; Szuta, Mariusz; Tomaszewska, Romana; Stypułkowska, Jadwiga; Alobaide, Hiba; Świerzy, Marta; Kaczmarzyk, Tomasz (Journal of Stomatology, 2018)
Central mucoepidermoid carcinoma (CMEC) is a very rare neoplasm comprising 2% to 4% of all mucoepidermoid carcinomas. We herby present an unusual case of high-grade CMEC of the maxilla of a 53-year-old male patient, who was referred to the Department of Oral Surgery by a general dentist due to accidentally detected on X-ray unilocular radiolucent lesion on the premolar region of the left maxilla. Intraoral examination revealed asymmetry of the vestibule with palpable swelling in the region of 24-26 with a positive fluctuation and crepitation. After CBCT examination and core needle biopsy, preliminary diagnosis of residual cyst was made, and the cystic lesion was excochleated. Histopathological examination revealed a high-grade CMEC. Patient was reported to the Department of Cranio-Maxillofacial Surgery, where he underwent a subtotal maxillectomy and selective neck dissection. The patient remains in follow-up, having had no recurrences during 12-month period after surgery.